Analysis of parallel connected Fibonacci switched capacitor converter - Wanglok Do; Kei Eguchi (Energy Reports, 2020)
Switched capacitor converter (SCC) is a power converter without magnetic components. SCCs have been used in various portable electric products such as flash memories and energy harvesting systems. Conservative SCCs separately charge and discharge their output capacitors during one operating cycle. This operation reduces power efficiencies and increases output ripple voltages. To improve this problem, a parallel connected Fibonacci SCC (PFSCC) was suggested. The symmetric structure of the PFSCC can lead to its better output performance. As a preliminary stage to design a hardware and a controller for the PFSCC, this paper performs an analysis of the PFSCC to derive parameters such as its optimized capacitance and power stage transfer function. Also, simulations and comparisons with 4 different SCCs are conducted to verify its performance.
Keywords: 330; Circuit modeling; Component optimizing; Switched capacitor converter; Symmetric structure